Sosialisasi Proses Implementasi Deep Learning dalam Pembelajaran Bahasa: Mewujudkan Pengalaman belajar yang Bermakna, Reflektif, dan Menyenangkan - Mulyani, Martina; Widaningsih, Sri; Wiyati, Retno; Novianti, Alviaderi; Darmana, Feniawati (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
21st-century learning demands mastery of critical thinking, creativity, communication, and collaboration skills. However, these skills are difficult to develop if the learning approach still focuses on lectures and memorization. Deep learning, which emphasizes meaningful understanding, reflection, and application in real life, is one potential strategy for bridging this gap. Unfortunately, most previous research has only examined deep learning in digital contexts, although many schools in Indonesia still have limited access to technology. The service aims to socialize the process of implementing deep learning that can be applied in classroom environments with limited access to technology, especially to describe student interactions that represent their skills in understanding, applying, and reflecting. With a socialization approach using two stages of activities, namely the process of implementing activities and evaluation, activities were carried out for grade 11 students at SMA Swadaya Karya Ciwidey, Bandung Regency. The results show that the application of deep learning-based learning encourages students to understand concepts more critically (such as distinguishing between laziness and procrastination), relate the material to authentic experiences, and develop reflective problem-solving strategies. College students also show improvements in engagement, self-awareness, and high-level thinking skills, even without the support of digital technology. This study underscores the importance of learning designs that focus on immersive learning experiences that are relevant to students' lives, even in the context of limited resources.